Healthcare providers' perspectives on expedited partner therapy for chlamydia: a qualitative study. (19th March 2015) - Rosenfeld, Elian A; Marx, John; Terry, Martha A; Stall, Ron; Pallatino, Chelsea; Miller, Elizabeth
Abstract : Objectives: Expedited partner therapy (EPT) effectively reduces rates of reinfection with chlamydia and increases the number of partners treated for the infection. Healthcare provider (HCP) provision of EPT is low. The objective of this qualitative study was to understand HCP views and opinions regarding the use of EPT in a state where EPT is permissible but underused. Methods: Using a purposive sampling strategy to include diverse HCPs who treat young women at risk for chlamydia, 23 semistructured, in-depth interviews were conducted between October and December 2013. The interviews included questions about knowledge, attitudes, experiences with, and barriers and facilitators regarding the use of EPT. Results: Many respondents report using EPT and believe the practice is beneficial for their patients. Most providers were unaware of their colleagues' practices and had limited knowledge regarding institutional policies around EPT. HCPs noted a variety of barriers, such as fear of liability, confusion around the legal status of EPT and not being able to counsel patients' partners that make routine use of this practice a challenge. Facilitators of EPT include speaking on the phone with patients' partners and establishing legislation enabling EPT. Conclusions: This is the first study to qualitatively examine HCPs' perspectives on EPT in the USA. Barriers to EPT, including concerns about counselling patients' partners and the legal status of EPT, can be overcome. EPT recommendations could include the use of phone calls as part of their guidelines. Changing EPT legislation at the state level in the USA is an important factor to facilitate EPT use.